Fostering Civil Public Dialogue Through Collaboration: Opportunities for Extension - William A. Warren ([TEST] Journal of Extension, 2021)
This article addresses the issue of incivility in public policy debates by pointing to citizen collaboratives as an alternative that promotes civil dialogue. Collaboration forums bring together those having diverse and often opposing interests to craft solutions to public policy issues intended to advance all parties’ interests in an atmosphere of mutual trust, mutual learning, and respect. Extension has a role to play through engagement with collaboratives to build community capacity and advance community and ecological sustainability. Examples of Extension involvement and the potential success that collaboratives can achieve is presented.
Keywords: collaboration; collaborative; civil dialogue; community development; natural resources